2006
DOI: 10.1002/pola.21636
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel fully aliphatic polyimidosiloxanes based on alicyclic or adamantyl diamines

Abstract: A series of fully aliphatic polyimidosiloxanes (APISiO) were prepared by poly(addition/condensation) reaction of bicyclo [2,2,2] oct‐7‐ene‐2,3,5,6‐tetracarboxylic dianhydride or cyclobutane‐1,2,3,4‐tetracarboxylic dianhydride and varying compositions of 1,3‐bis (3‐amino propyl)‐tetra methyl disiloxane and rigid adamantyl diamines (1,3‐diaminoadamantane or 3,3′‐diamino‐1,1′‐diadamantane) or flexible alicyclic diamines (4,4′‐methylene bis(cyclohexylamine) or 4,4′‐methylene bis(2‐methylcyclohexylamine)). High tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 52 publications
0
37
0
Order By: Relevance
“…29 Generally, as the degree of backbone flexibility increases and/or as the degree of intermolecular interactions decreases the polymer solubility increases. Because DAn and CPDA are rigid while BTDA is relatively flexible, the degree of backbone flexibility of the polyimides would decrease with increasing content of DAn or CPDA unit.…”
Section: Resultsmentioning
confidence: 99%
“…29 Generally, as the degree of backbone flexibility increases and/or as the degree of intermolecular interactions decreases the polymer solubility increases. Because DAn and CPDA are rigid while BTDA is relatively flexible, the degree of backbone flexibility of the polyimides would decrease with increasing content of DAn or CPDA unit.…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric constants of PADMA, PTCDMA, and P(ADMA-co-TCDMA) were 2.18, 2.19 and 2.23, respectively, all of which were lower than that of PMMA (3.44). The lower dielectric constants of PADMA, PTCDMA and P(ADMA-co-TCDMA) 21 were attributed to the fact that adamantane and tricyclodecane are fully-aliphatic hydrocarbons, and thus lead to low hydrophobicity and polarity [33]. It was observed that the dielectric constant of P(ADMA-co-TCDMA) was slightly higher than those of PADMA and PTCDMA.…”
Section: Dielectric and Moisture Absorption Propertiesmentioning
confidence: 98%
“…Polyimide structure modification has extensively been studied for this purpose. Typical methods of the chemical modification involve the incorporation of fluorine substituents, 2,4-6 alicyclic structures, [7][8][9][10][11][12][13][14][15] and other bulky groups. 16 On the other hand, the introduction of nanopores into a polyimide film has been reported to be an effective way to lower its dielectric constant.…”
Section: Introductionmentioning
confidence: 99%